Authentic Assessment For Improving The Quality Of Learning - Musthofa Musthofa (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2020)
This research aims to determine the phenomenon of authentic assessment implementation in improving learning quality. The method used in this study uses library research or research literature. The study concluded that authentic assessments with project-based learning and problem-based learning approach could improve the learning quality, giving positive implications for the development of human resources. For example, building competence, positive, critical thinking, innovative, and doing work in the form of products. Thus, an authentic assessment (project-based learning, problem-based learning, and product assessment) can improve the quality of learning to give implications for the development of human resources in the future.AbstrakPenelitian ini bertujuan untuk mengetahui fenomena implementasi asesmen otentik dalam meningkatkan kualitas pembelajaran. Metode yang digunakan dalam penelitian ini menggunakan penelitian kepustakaan atau literatur penelitian. Studi ini menyimpulkan bahwa penilaian otentik dengan pembelajaran berbasis proyek dan pendekatan pembelajaran berbasis masalah dapat meningkatkan kualitas pembelajaran, memberikan implikasi positif untuk pengembangan sumber daya manusia. Misalnya, membangun kompetensi, berpikir positif, kritis, inovatif, dan melakukan pekerjaan dalam bentuk produk. Dengan demikian, penilaian otentik (pembelajaran berbasis proyek, pembelajaran berbasis masalah, dan penilaian produk) dapat meningkatkan kualitas pembelajaran untuk memberikan implikasi bagi pengembangan sumber daya manusia di masa depan.